An Experimental Study to Investigate the Effect of Biopolymer-Treated Layers on the Lateral Earth Pressure of Retaining Wall Backfill - Kim, Gi Yun; Lee, Haejin; Cho, Gye Chun; Chang, Ilhan (Geotechnical Special Publication, 2023)
In retaining wall design, the Coulomb and Rankine active earth pressure theories is commonly used. However, because the above theories include various assumptions, determining the accurate earth pressure distribution acting on the retaining wall is limited. When estimating the earth pressure of a retaining wall, it is commonly assumed that the backfill material is cohesionless; nevertheless, the cohesion force occurs in the direction of resisting sliding, and the active earth pressure decreases. Many research studies have recently been performed to reduce the earth pressure acting on the retaining wall through various materials and the active earth pressure taking cohesion materials into account. In this study, a soil tank apparatus which has a rotatable wall on the side is used to assess the lateral earth pressure of different backfill conditions with wall rotation. The lateral earth pressure according to the rotation of the wall was measured, and the earth pressure reduction effect was verified by forming BPST (biopolymer-based soil treatment) layers that can vary the shear strength parameter in the sandy soil. The lateral earth pressure rapidly decreased as the wall started to rotate. The improvement effect of the shear strength parameter was negligible in the wet (initial) condition of the BPST, and hence had little effect on the lateral earth pressure behavior. However, the lateral earth pressure reduction effect occurred in the BPST dehydrated (dried) condition by restricting the lateral movement of soil particles by improving cohesion and working similarly to the relief shelf of the retaining wall.
Keywords: Active earth pressure; Condition; Lateral earth pressure; Pressure reduction; Reduction effects; Retaining wall design; Shear strength parameters; Soil treatments; Wall backfill